Canadian nuclear energy policy : changing ideas, institutions, and interests - Dorman, Arslan; Morrison, Robert W.; Doern, G. Bruce (University of Toronto Press, 2001)
Focusing on the federal government, but with special attention given to key changes in Ontario, the analytical core of this book identifies five key nuclear energy choices and challenges that face the federal government and other Canadian policy makers.